Prevalence, risk factors and outcomes of acute kidney injury in critically ill children with hematological malignancies - Tariq, Rabeea; Haq, Anwar U.; Ahmed, Abdul R.; Saeed, Arsalan; Khan, Mohammad R. (International Journal of Contemporary Pediatrics, 2024)
Background: Limited data is available on acute kidney injury (AKI) in critically ill children with hematological malignancies. The aim of this study is to assess the rate, risk factors and outcome of AKI in children with hematological malignancies admitted in the pediatric intensive care unit (PICU) of a large tertiary-care pediatric oncology referral center in Karachi. Methods: We conducted a retrospective, cross-sectional study on critically ill children with hematological malignancies who developed AKI and were admitted in PICU from July 2017 to June 2019. Demographic data, clinical profile, and outcomes were included. AKI was defined according to the kidney disease: improving global outcomes (KIDGO) criteria. Results: Of 399 critically ill children with a hematological malignancy, 85 (21.33%) patients developed AKI. The mean age was 7.8±3.8 years and 66% were male. The most common diagnosis was acute lymphoblastic leukemia (ALL) (50%). Dialyitc therapy was initiated in 9 patients (2.3%) only. The risk factors for AKI were tumor lysis syndrome (p=0.001), exposure to nephrotoxic drugs (p<0.001), septic shock (p<0.001), use of mechanical ventilation (p<0.001), need of vasoactive drugs (p<0.001) and age (p<0.001). Kaplan-Meier survival analysis showed that median survival time in children with AKI was 11 days (95% CI 7.6–14.4) while median survival time in children without AKI is significantly higher (log rank test p<0.001). By multivariate analysis, AKI is an independent risk factor for mortality [OR 20.02; 95% CI 8.14-49.28; p<0.001]. The mortality rate was 63.5% in patients with AKI and 8.6% in patients without AKI (p<0.001). Conclusions: AKI occurred in 21.3% of critically ill children with hematological malignancies and is associated with age, organ dysfunction, sepsis, tumor lysis syndrome and exposure to nephrotoxic drugs. AKI is an independent risk factor for high mortality rate in this population.